Plastic Waste Management Education Through the Waste Management Unit (UPS) in Borobudur Village - Adhi Surya Perdana; Indah Riadi Putri; Fatwa Nurul Hakim; Rastono Rastono; Yuniyati Yuniyati; Sholikin Sholikin; Arina Waliyati (FITK UIN Walisongo Semarang, 2023)
The rapid increase in population and tourist visits can be the basis of an important issue of increasing waste volume as one of the causes of environmental problems, one of which will affect people's consumption patterns so that it has an impact on increasing the volume, type and characteristics of waste. The purpose of this study: how is the level of awareness of community function duties in waste management, how is the role, involvement, participation or participation of the community in supporting waste management, and how is the support or synergy of other stakeholders in waste management in Borobudur Magelang District. The research method used is quantitative ex-post facto in focus group discussion (FGD) activities by presenting 40 people (representatives of 21 hamlets in Borobudur Village). The results of the research on Borobudur Village area-based waste management, waste management policies and regulations, and inorganic waste management (plastic) obtained the results there is a significant difference in changes in insight, knowledge and understanding before and after FGD activities on plastic waste management into various creations. The conclusion is that the level of awareness, understanding, role, involvement and participation of community waste management institutions and the community positively support the wise management of plastic waste in the form of various creations